2022
DOI: 10.1186/s12888-022-03783-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of common mental disorders and factors associated among people living in Addis Ababa Ethiopia 2018: community based cross-sectional study

Abstract: Background Common mental disorders are a group of distress states manifesting with anxiety, depressive and unexplained somatic symptoms, affecting individuals in different age groups, causes suffering to the individuals, families and community. Objective This study assessed the magnitude of Common mental disorder and associated factors among people living in Addis Ababa, Ethiopia. Methods Community bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…World Health Organization (WHO) report shows that 4,480,113 (4.7%) and 3,139,003 (3.3%) people in Ethiopia are estimated to suffer from depression and anxiety respectively; the total years lived with a disability was about 837,683 (10.1%) led by depressive disorder and 292,650 (3.6%) by anxiety disorder (2). Previous cross-sectional community-based studies in Jimma Town, South West Ethiopia, Illu Ababor zone, southwest Ethiopia, Silte Zone, Southern Ethiopia, in Addis Ababa, and Harari Regional State, Eastern Ethiopia reported that the prevalence of CMD among adult residents was 33.6%, 27.2%, 39.7%, 24.7%, and 14.9%, respectively (10)(11)(12)(13)(14). These past studies more focused on the southern part of Ethiopia and could not give national representative data.…”
Section: Introductionmentioning
confidence: 97%
“…World Health Organization (WHO) report shows that 4,480,113 (4.7%) and 3,139,003 (3.3%) people in Ethiopia are estimated to suffer from depression and anxiety respectively; the total years lived with a disability was about 837,683 (10.1%) led by depressive disorder and 292,650 (3.6%) by anxiety disorder (2). Previous cross-sectional community-based studies in Jimma Town, South West Ethiopia, Illu Ababor zone, southwest Ethiopia, Silte Zone, Southern Ethiopia, in Addis Ababa, and Harari Regional State, Eastern Ethiopia reported that the prevalence of CMD among adult residents was 33.6%, 27.2%, 39.7%, 24.7%, and 14.9%, respectively (10)(11)(12)(13)(14). These past studies more focused on the southern part of Ethiopia and could not give national representative data.…”
Section: Introductionmentioning
confidence: 97%
“…According to existing literature, many factors have been associated with poor mental health status among urban people, including gender, marital status, daily labour, chronic medical illness, advanced age, ethnicity and low income. 7 8 The prevalence of mental disorders among Chinese residents has been reported to be approximately 9.3% in a given year. 9 The prevalence of anxiety disorder among elderly patients with hypertension in Shanghai has grown up to 17.2% in the given 2 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the incidence of ADs among male individuals increased rapidly during 2005-2010 and continued to increase until 2019 according to joinpoint analysis. This may be due to environmental changes and a more rapid pace of life [39,40]. During the study period, the world experienced a bird flu pandemic, rising oil prices, repeated terrorist attacks, and more severe natural disasters [41][42][43][44].…”
Section: Principal Findingsmentioning
confidence: 99%